Comparative Studies of Lead and Chromium Concentration in Red Chili and Turmeric Powder: Short Communication: Concentration of Lead and Chromium in Red Chilli Powder - Khalid, Sara; Tufail, Shahid; Hussain, Shabbir; Iqbal, Muhammad (Biological Sciences - PJSIR, 2021)
The red chili and turmeric powder available commercially in Lahore supermarkets which were randomly analyzed to evaluate the lead (Pb), and chromium (Cr) concentration by atomic absorption spectrometric technique. Lead and chromium were found to be in the ranges of 0.0050-0.01 ppm and 0.0430-0.1482 ppm, respectively. The mean concentration of lead in the red chili and turmeric powders were found to be 2.6 mg/Kg and 5.3 mg/Kg respectively, while that of the chromium was found to be 0.0419 mg/Kg and 0.1142 mg/Kg respectively. Levels of both these metals (lead and chromium) are therefore lower in the red chili compared to the turmeric powder. Also, both the samples are comparatively rich in lead as compared to chromium.